Relationship between Glutathione S-transferase gene polymorphisms and clinical features of psoriasis: A case-control study in the Turkish population - Hatice Gül Dursun; Recep Dursun; ilknur Çınar Ayan; Ayşe Gül Zamani; Mahmur Selman Yıldırım (Galenos Publishing House, 2024)
Background and Design: In this study, we investigated whether Glutathione S-transferase Mu 1 (GSTM1) and Glutathione S-transferase Pi 1 (GSTP1) gene polymorphisms are risk factors for psoriasis development and characteristics of psoriasis. Materials and Methods: Venous blood samples were collected from both the patients and control subjects into 2 mL EDTA tubes. DNA was isolated from 260 psoriasis patients and 200 healthy control subjects, and GSTM1 and GSTP1 gene polymorphisms were genotyped by realtime polymerase chain reaction method. Results: According to the analysis results, although the frequency of the GSTM1 null genotype was 1.33 times higher in patients compared to controls, this difference was statistically insignificant [95% confidence interval (CI): 0.91-1.93, p=0.13]. GSTP1 AG heterozygous genotype and GG homozygous polymorphic genotype frequencies also did not differ between patients and controls [odds ratio (OR): 0.80, 95% CI: 0.55-1.18, p=0.27 for AG genotype; OR: 0.74, 95% CI: 0.35-1.56, p=0.42 for GG genotype]. When both polymorphisms were evaluated based on the onset age and severity of the disease, no significant difference was found between the early onset age group and the late onset age group, nor between the mild group and the severe group. Conclusion: The results show that GSTM1 and GSTP1 polymorphisms do not have a major effect on the etiopathogenesis and clinical characteristics of psoriasis.